Plant Identification at SMAN 10 Makassar as a Learning Resource Based on Outdoor Learning on The Material of Plantae - Ince Rabiah Al Adwiah; Andi Faridah Arsal; Syamsiah Syamsiah (Biology Teaching and Learning, 2026)
AbstractPurpose: This study aims to identify the diversity of plant species found in the SMAN 10 Makassar environment and to assess their potential as outdoor learning resources for the Plantae topic.Research Methodology: This study was conducted at SMAN 10 Makassar from November 20 to December 31, 2025. The study used a qualitative descriptive approach, with data collection techniques including field observations, photographic documentation, and interviews. The instruments used included observation sheets and interview guidelines validated by expert lecturers. Data were analyzed using qualitative descriptive methods in the form of narrative descriptions.Results: The study showed that there were 58 plant species belonging to 6 classes and 35 families, scattered throughout various school areas such as parks, gardens, and yards. These plants have the potential to serve as learning resources to support students' understanding of the Plantae topic.Conclusion: The school environment of SMAN 10 Makassar boasts a diverse range of plants that can be optimally utilized as a learning resource based on outdoor learning, thereby increasing student participation, motivation, and observation and analytical skills.Limitations: This study was limited to one school location and examined only one variable, so the results cannot be broadly generalized.Contribution: This study contributes to the field of biology education, particularly in the development of environment-based learning (outdoor learning), and serves as a reference for teachers and researchers in utilizing the school environment as a contextual and interactive learning resource.Keywords: Plant Identification, SMAN 10 Makassar, Learning Resources, Outdoor Learning, Plantae, School Environment